Selection of rubber clones for resistance to South American leaf blight and latex yield in the germplasm of the Michelin plantation of Bahia(Brazil) - Garcia D; Goncalves P De S; Guen V Le; Mattos C R R (Journal of Rubber Research, 2004)
South American Leaf Blight (SALB), caused by an ascomycete fungus, Microcyclus ulei Henn is one of the most serios disease in Hevea spp. Although it is not found in South-East Asia and Africa, it is nevertheless a potential threat for these regions which account for over 98;of world rubber production. SALB resistance and latex yield were measured in a rubber tree clonal trial planted at Itubera (Bahia, Brazil), on 36 different clones coming from the germplasm of the Michelin plantation of Bahia. The clones were evaluated for their resistance to SALB during the first two years after planting. Inoculation tests and trials of the resistance during collection were carried out to confirm the trial observations. Latex yield was estimated on five-year-old rubber trees and architecture of the truck and the capony, structural traits of the laticiferous system were taken into consideration for the ultimate selection. This study indicated that few clones which were high yielding were also SALB resistant. The clones MDX 624, FDR 5788, CD 1130, MDX 607, CDC 312, FDR 5665, FDR 5802, CD 1174 were selected and will be studied in a large-scale clonal trial.
Keywords: Brazil; Breeding; Disease; Germplasm; Hevea brasiliensis; Latex yield; Microcyclus ulei; Resistnace; SALB